Role of Second Quinone Binding Site in Proton Pumping by Respiratory Complex I - Outi Haapanen; Amina Djurabekova; Vivek Sharma; Vivek Sharma (Frontiers in Chemistry, 2019)
Respiratory complex I performs the reduction of quinone (Q) to quinol (QH2) and pumps protons across the membrane. Structural data on complex I have provided spectacular insights into the electron and proton transfer paths, as well as into the long (~30 Å) and unique substrate binding channel. However, due to missing structural information on Q binding modes, it remains unclear how Q reduction drives long range (~20 nm) redox-coupled proton pumping in complex I. Here we applied multiscale computational approaches to study the dynamics and redox chemistry of Q and QH2. Based on tens of microseconds of atomistic molecular dynamics (MD) simulations of bacterial and mitochondrial complex I, we find that the dynamics of Q is remarkably rapid and it diffuses from the N2 binding site to another stable site near the entrance of the Q channel in microseconds. Analysis of simulation trajectories also reveal the presence of yet another Q binding site 25–30 Å from the N2 center, which is in remarkable agreement with the electron density observed in recent cryo electron microscopy structure of complex I from Yarrowia lipolytica. Quantum chemical computations on the two Q binding sites closer to the entrance of the Q tunnel reveal redox-coupled protonation reactions that may be important in driving the proton pump of complex I.